2007
DOI: 10.2214/ajr.06.0389
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Biopsy for the Diagnosis of Renal Tumors Before Treatment with Percutaneous Ablation

Abstract: Less than 5% of samples in our study were benign, and 11.8% were nondiagnostic. Biopsy in smaller lesions was less accurate; therefore biopsy is less useful for these renal lesions. Because fine-needle aspiration (FNA) has higher sensitivity than core biopsy, an appropriate algorithm may be to begin with FNA and reserve core biopsy for cases in which an onsite cytotechnologist is unavailable or deems the sample of inadequate cellularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 30 publications
2
27
0
1
Order By: Relevance
“…However there are also other benefits described in the literature, for example better visibility on US or CT guidance (due both to the greater number of acoustic interfaces, and to the slightly larger needle size), shorter procedure time and a 15% increase in biopsy technical success [16]. As for diagnostic accuracy, our experience confirms the studies conducted so far, that calculated the positive predictive value of pretreatment SRM biopsy to be between 95 and 100%, with accuracy between 84% and 97% [10,19,20,[22][23][24][25][26] (Table 3). In our series the 2-cm cutoff approaches statistical significance for diagnostic accuracy; this is probably due to the difficulty in visualising smaller lesions with the imaging guide during biopsy, especially when the lesion is intraparenchymal; thus we believe that this could remain a valid cut-off for a prospective study on diagnostic accuracy of needle biopsy for SRM.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However there are also other benefits described in the literature, for example better visibility on US or CT guidance (due both to the greater number of acoustic interfaces, and to the slightly larger needle size), shorter procedure time and a 15% increase in biopsy technical success [16]. As for diagnostic accuracy, our experience confirms the studies conducted so far, that calculated the positive predictive value of pretreatment SRM biopsy to be between 95 and 100%, with accuracy between 84% and 97% [10,19,20,[22][23][24][25][26] (Table 3). In our series the 2-cm cutoff approaches statistical significance for diagnostic accuracy; this is probably due to the difficulty in visualising smaller lesions with the imaging guide during biopsy, especially when the lesion is intraparenchymal; thus we believe that this could remain a valid cut-off for a prospective study on diagnostic accuracy of needle biopsy for SRM.…”
Section: Discussionsupporting
confidence: 84%
“…In fact most authors [24,25,27] describe a greater sensitivity of CB, except Heilbrun et al, who reported a greater sensitivity of FNAB [26]. However, these authors use a 20G needle for CB, unlike most of the others, who used 18G needles; furthermore Heilbrun's case series is not among the largest ones.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies reported that percutaneous renal mass biopsy achieved high diagnostic rates ranging from 84%-97% (2,13,15,17,18,25). All of these studies included larger renal masses (4 4 cm) as well as SRMs.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) is usually used to guide renal mass biopsy, and it can aid in diagnosis in 79%-97% of cases (13)(14)(15). However, ultrasound (US) guidance offers numerous advantages over CT guidance for biopsy, including (a) lack of ionizing radiation, (b) real-time visualization of the needle, and (c) relatively lower cost (3).…”
mentioning
confidence: 99%
“…Future trials should confirm the malignant status of the lesion prior to ablation. Same-day biopsy and ablation may be up 50 % less expensive than a 2-day procedure because of the multiple procedure payment reduction Medicare rule [10].…”
Section: Renal Masses Prior To Ablative Therapymentioning
confidence: 99%